Os evangélicos e a política: Itinerários e lógicas do engajamento político de líderes pentecostais da Igreja Assembleia de Deus em Imperatriz-MA - OLIVEIRA JUNIOR , Bezaliel Alves (2021)
vThe objective of this work is to analyze the careers and individual logics of political engagement of leaders of the Evangelical Church Assembly of God (IEADI) in Imperatriz - Maranhão, who were notable for their investments in conventional spaces and instances of politics, such as parties and elections. It is, then, about trying to apprehend the production dynamics of political participation with a focus on the credentials, competences and social and symbolic resources considered necessary for that. Thus, to try to capture the modalities, processes and conditions of the political and religious engagement of these agents, we resorted to varied methodological strategies: exploration of channels and social networks used by the institution; institutional documents and representations produced by the institution regarding its past; participation in conventions and monitoring of debates regarding the choice of candidates approved by the institution and, fundamentally, conducting in-depth interviews with agents renowned in the region for their investments and transitions between the religious and political spheres within the IEADI/MA. Thus, this dissertation was divided into three interdependent chapters. In the first, based on the available bibliography on the subject, we look at the issue of the relationship between religion and politics in Brazil with a focus on changes in the public and political presence strategies of Pentecostal Churches. In a second moment, we sought to monitor the institutionalization process of the Assembly of God Church in Brazil and Maranhão, using both researchers who have been investigating the topic, as well as interpreters and intellectuals from the institution, whose works analyze the registration process. in the cut-out space. The last chapter, in turn, examines institutional strategies, the institution's relationship with parties, and the profiles and perceptions of leaders who are notable for their investment and/or involvement in the political sphere. Throughout the dissertation, we intend to demonstrate how this more general issue regarding the modalities of political participation of evangelicals can be observed from a more local and specific context, which at the same time refracts the strong penetration of the evangelical segment with the popular classes, at the same time that they depend on conjunctural, organizational and personal variations that affect the conditions of political participation in the context in question.